Strategi Pemasaran Produk Suvenir Pendukung Desa Wisata Tinalah Dan Program Bela Beli Kulon Progo - Anggi Rahajeng (Pengabdian dan Pengembangan Masyarakat Sekolah Vokasi UGM, 2018)
This paper aims to provide an analysis of the activities of community service performed to increase the income of rural communities by modified inhouse training marketing strategy of supporting souvenir products of Tinalah Tourism Village, Purwoharjo Samigaluh Kulon Progo. The majority of Purwoharjo villagers work in primary sectors such as agriculture and livestock, the income of the population is relatively low, so look for alternative work by developing Desa Wisata Tinalah. The addition and / or change of livelihoods of the primary sector that sells goods to the tourism sector that sells services require adaptation processes especially in terms of providing services to visitors / tourists. Making village tourism souvenirs requires skills to market products to tourists so that satisfaction can be met optimally. Therefore, the team of the Department of Economics and Business, Vocational College UGM held a marketing strategy training for souvenir product of Tinalah Tourism Village which is later expected to increase the income of the villagers. This training was given to all members of Tinalah Village and some Purwoharjo Village Government Staff. Marketing strategy that used both offline and online (making email account and blog) towards e-smart SMEs thus they may involve in online market place. The expected outcome of this community service activity is increasing skill of the business actor in marketing the souvenir products supporting the tourist village to meet the optimum tourist satisfaction in order to increase the income of Purwoharjo village community.